(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يعتبر نظام التحكيم أسلوباً بديلاً عن القضاء يلجأ إليه أطراف العلاقة القانونية عند حدوث منازعة بينهم لتجنب إجراءات القضاء الطويلة، ونظام التحكيم معمول به في البورصات العالمية كبورصة لندن ونيويورك وأخذت به البورصات العربية كذلك لكونه يتناسب مع سرعة الحياة التجارية والاقتصادية من جهة ، وآلية عمل البورصة التي تمتاز بالسرعة في اتخاذ قرارات البيع والشراء من جهة أخرى، الأمر الذي يستلزم ان تكون طريقة حل النزاعات التي قد تنشأ بآلية مشابهة ومواكبة لهذه السرعة أيضا. وقد نص قانون سوق دمشق للأوراق المالية على نظام التحكيم كأسلوب إجباري لفض المنازعات التي لاتكون السوق طرفاً فيها وفق شروط معينة وفق أحكام المادة /71/ من القانون رقم /55/ لعام 2006م، إلا أنّ هذا النظام منتقد لمخالفته الدستور السوري الذي يكفل حق التقاضي للأطراف كافة، إضافة لكونه يهدم جوهر التحكيم الذي يقوم على أساس الاتفاق بين الأطراف وإرادتهم الحرة. وينتقد المشرع السوري أيضاً على مسألة سكوته عن اختصاص القضاء في حل منازعات البورصة حيث لم يحدد الجهة القضائية المختصة مما يستدعي تدخلاً تشريعياً لسد هذا النقص التشريعي بشكل يتوافق مع نصوص الدستور التي تعتبر قمة الهرم القانوني في أي دولة ولغلق الباب أمام الاختلاف الفقهي الحاصل بين أساتذة القانون السوري في مسألة اختصاص القضاء في النظر بمنازعات البورصة من عدمه. لذا نأمل أن يشكل هذا البحث بداية لوضع قواعد قانونية جديدة تنظم مسألة حل المنازعات في البورصة دون إغفال اختصاص القضاء ودون فرض التحكيم جبراً بشكل يخالف النصوص الدستورية. Arbitration system is an alternative way for the judiciary to turn to the parties in the legal relationship when a dispute occurred between them in order to get rid of long-judiciary procedures, the arbitration system used in the global stock markets being commensurate with the speed of business and economic life on the one hand, and the mechanism of the stock market characterized by the speed in making buy and sell decisions of Action On the other hand, which requires to be a way to resolve disputes that may arise similar mechanism and to keep up with this speed, too. Damascus Securities Exchange Act provides for arbitration as a way mandatory system of dispute resolution that not be the market party under certain conditions in according with the provision of Article \71 of law \55 2006, but this system critic from the point of violation of the Syrian Constitution, which guarantees the right of litigation for all parties, in addition to being destroys the essence of arbitration which is based on the agreement between the parties and their free will. Syrian lawmaker criticizes as well as on the issue of silence about the competence of the judiciary in resolving disputes bourse where did not specify the competent judicial authority, which requires intervention legislatively to fill this legislative shortfall in a manner consistent with the provisions of the Constitution, which is the top of the legal pyramid in any country and suspended the door to the difference idiosyncratic winning among law professors Syrian on the competence of the judiciary to consider disputes the stock market or not.